Adopsi Teknologi Petani pada Sekolah Lapangan Pengelolaan Tanaman Terpadu (SL-PTT) - Karmila Muchtar; Djoko Susanto; Ninuk Purnaningsih (Jurnal Penyuluhan, 2015)
Field School of Comprehensive Agriculture Land-Use Management (SL-PTT) is agriculture innovation from ministry of agriculture. The SL-PTT program aims accelerating the adoption of innovation at the farm level to increase production in a sustainable manner. The study aims to analyze decision making process by the farmers to adopt and utilize the technology of rice innovation in their land-use and and how much the production level of rice achieved by the farmers in SL-PTT program. The study was planned using survey descriptive correlational on March-April 2014 covered 80 farmers in village of Abbokongeng, Sub District of Kulo, District of Sidrap, South Sulawesi. Data were analyzed and tested using multiple linear regression. The evidence showed that almost all (91,25%) of the farmers applied all innovations, such as: using high qualified seeds, planting system, using appropriate fertilizer and water irrigarion, controlling pests, harvest and past-harvest management. Production of rice were more than 6,000 kg /ha with average profit is Rp 18,969,950/Ha. To increase adoption innovation of technology by the farmers, exntension worker should carry out more intensive approach. Communication between the farmers and the extension worker should be maintained and increased through the SL-PTT program in such that the rice production can be consistently increazed.Keywords: Adoption, technology, farmer, extension worker, SL-PTT